Decentralisation in Morocco: the current reform and its possible contribution to political liberalisation - Annabelle Houdret; Astrid Harnisch (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
In reaction to the political unrest of 2011, the government and King of Morocco promised comprehensive political change; in particular, the decentralisation reform was intended to enhance the political participation of the population and make the work of state institutions more efficient and transparent. Important democratic principles such as participation and accountability are also backed by the 2011 constitution. New laws for decentralisation reform and the first regional elections in 2015 laid key foundations for change. Six years later however, it is evident that the process of implementation has been delayed significantly. Against the background of international experiences in this field, the discussion paper revels three bundles of factors that need to improve to make decentralization work and enhance the chances for political liberalization: Firstly, the current political economy of the process is clearly hindering the implementation of the reform; key laws and regulations have yet to be passed, for example to regulate the distribution of power and participation processes in detail. The closely associated distribution of social resources such as influence, money and legitimacy is still negotiated between the royal house, the government and the various elites. Secondly, many relevant public institutions, be they administrations or political decision-makers, cannot fulfil the tasks assigned within the scope of the reform, due to a lack of autonomy, competencies and resources. Moreover, the structure of the political system limits the autonomy and scope of action of the elected institutions. And thirdly, the information and participation of the population remain inadequate and would need to be strengthened to make decentralization and political liberalization work.
Keywords: 330; Governance; Democracy and Autocracy